Monsters and magic - Ross, Stewart; Phillipps, Francis (Brookfield, Conn. : Copper Beech Books, 1998)
A collection of tales drawn from across North and South America and including those of native peoples as well as of later settlers.
John Henry -- Brer Rabbit thinks fast -- Pocahontas -- Wishpoosh and the trickster god -- Glooskap meets his match -- Sedna the Terrible -- Moby Dick -- Sleepy Hollow -- The shame of Quetzacoatl -- Hiawatha -- Paul Bunyan's wife -- Bird Boy.
Keywords: Tales; Folklore